Penguatan Komunikasi Efektif dalam Proses Pembelajaran Melalui Pelatihan untuk Guru di MA Al Fakhriyah - Elim Halimatusadiyah; Syifaul Husna (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2024)
To create interactive and meaningful learning, educators must possess effective communication skills. The purpose of this article is to improve the communication skills of teachers at one of the high schools in Bandung Regency. This community service activity uses a training and mentoring method based on practice along with qualitative evaluation. The results of the activity show that teachers have gained a better understanding of effective communication techniques and how to use them in classroom management. In addition, students showed a positive response to the changes made by the teacher. In addition, this article discusses the role of activities in improving the quality of education at the upper secondary level.